Strategi Pemasaran Digital SMP Muhammadiyah 1 Surakarta untuk Meningkatkan Daya Saing di Era Revolusi Industri 4.0 - Kusyairi, Mochamad Irsyad; Rohid, Burhannudin; Hidayat, Fahmi (Lembaga Yasin AlSys, 2025)
The limited number of studies on digital marketing and branding strategies in faith-based secondary educational institutions serves as the background for this research, particularly considering their crucial role in enhancing school competitiveness in the era of the Fourth Industrial Revolution. This study aims to analyze the implementation of digital marketing strategies through Instagram and the official website of SMP Muhammadiyah 1 Surakarta in strengthening brand identity and shaping a positive public image of the school. A qualitative approach with a case study design was employed, involving purposively selected participants comprising the principal, teachers, and public relations staff. Data were collected through semi-structured interviews, field observations, and digital document analysis, and subsequently analyzed using Miles & Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. The main findings indicate that visual strategies and digital content distributed via Instagram and the school’s website play a significant role in building a positive image and enhancing public trust, despite identified weaknesses in message consistency and audience engagement. These findings support digital branding theory, which emphasizes the importance of integrating visual identity, institutional narrative, and technology-based communication strategies. The study concludes that synergy between the digital school concept and digital marketing is a key factor in achieving sustainable school competitiveness in the digital era. The implications of this research include theoretical contributions to the enrichment of digital branding studies within the context of secondary education, as well as practical recommendations for schools to strengthen digital content management, optimize search engine visibility, and maintain consistent visual identity across communication channels.